Analysis of meaning of Keisya Levronka's song Tak Ingin Usai - Sauma Nadia Azzahro; Sri Utami (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Abstract : This research focuses on the lexical and grammatical meanings in the lyrics of Keisya Levronka's song